Paracambi industrial: uma proposta de roteiro cultural - Pereira, Ronaldo Vicente (2018)
The objective of this dissertation is to investigate, within the world of cultural tourism, the possibility of elaborating a cultural itinerary in the city of Paracambi in the State of Rio de Janeiro. The mentioned municipality was developed from the appearance of three textile factories, especially the Textile Company Brazil Industrial, and an entire asset constituted in its more than one hundred years of activities in the region. The research is justified by the fact that Paracambi already develops ecological tourism, due to the natural diversity of the region. Add to that its proximity to the Fluminense Coffee Valley, a tourist route consecrated in the state. In this way, the elaboration of a cultural itinerary could be an important increase of the activities of tourism developed in the city. The reflections developed in this research were based on a multidisciplinary theoretical perspective involving Sociology (Keller 1997), Anthropology (Leite Lopes, 1988), Education and Work (Ciavatta, 2007), Historiography (Furtado, 2003; Silva 2009), Geography) and Cultural Tourism (Molleta 1998; Cordeiro 2006). The methodological proposal was based on literature review, field visits and interviews with residents of Paracambi who worked at Companhia Têxtil Brasil Industrial. At the end of the work, a proposal is presented for a cultural itinerary capable of relating the history of the said Factory and the city of Paracambi, which are merged; At the same time, research produces, besides a script, enough subsidies to establish a close correspondence between industrial patrimony and working memory.